Artificial Intelligence for .NET : speech, language, and search : building smart applications with Microsoft Cognitive Services APIs /: speech, language, and search : building smart applications with Microsoft Cognitive Services APIs. (2017) - Pathak, Nishith; Bhandari, Anurag
No abstract available